Peranan Guru Pendidikan Agama Islam Dalam Meningkatkan Akhlak Mulia Peserta Didik SMK Negeri 2 Binjai - Agustina, Henri; Alban, Alban; Mulyadi, Rahmad (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2024)
The aims of this research are: (1) To obtain an overview of the morals of students at SMK Negeri 2 Binjai; (2) To analyze the supporting and inhibiting factors in the implementation of improving the noble morals of students at SMK Negeri 2 Binjai; (3) To explain the efforts of Islamic Religious Education teachers in improving the noble morals of students at SMK Negeri 2 Binjai. This research was written using qualitative research methods with normative theological, pedagogical and psychological approaches. The research instruments are observation guidelines and interview guidelines. Data collection uses observation, interviews and documentation. The results of the research show that: (1) The morals of students at SMK Negeri 2 Binjai are good. This can be seen from the implementation of congregational prayers which are running smoothly, the implementation of the culture of greetings is also going according to expectations, every student when they meet the school community always say hello, including when entering class. Furthermore, the clean culture also works effectively, because students are always enthusiastic about participating in clean Saturdays and throw away rubbish in the right place; (2) The supporting factor for the implementation of improving the noble morals of students at SMK Negeri 2 Binjai is the full support of the school principal and teachers through example, adequate facilities and infrastructure such as prayer rooms and healthy canteens. Meanwhile, inhibiting factors are the social conditions of students' households, the environment outside of school and students who do not yet understand the importance of noble morals; (3) The efforts of Islamic religious education teachers to improve the noble morals of students at SMK Negeri 2 Binjai are to provide good examples regarding the implementation of the culture of greetings, clean culture and the habit of praying in congregation as well as providing sanctions for students who enter class without saying hello.